KONTRIBUSI KEKUATAN OTOT ANGGOTA GERAK ATAS FLEKSIBILITAS TOGOK DAN POWER TUNGKAI TERHADAP KEMAMPUAN SENAM LONCAT HARIMAU SISWA PUTRA - Heri Purwanto, Sulistyanto (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2013)
This study aims to determine the motion of the relations between upper moving muscle strength, Trunk flexibility, legspower in male students tiger jump gymnastic ability. This study is a correlation research methods and techniques bytaking survey data with the test and measurement. The population used in this study were all students of class XIson SMAN 1 Bantul. The instrument used is a test of upper limb muscle strength with spring scales , trunk flexibilitywith sit and reach fleksometer use tools , power tools limbs to test the ability of vertical jump and jump tiger with thecorrect phases , namely the initial stance , movement and attitude final implementation. To analyze the data collected,researchers used regression analysis techniques three predictors with a significance level of 5 %. The results showedthat: (1) There is a significant contribution between upper limb muscle strength of the movement to tiger jump withp = 0.025, (2) There is a significant contribution to the ability of the flexibility trunk tiger jump motion with p = 0.021, (3) There is a significant contribution to the ability of the power limb motion tiger jump with p = 0.031, (4) There isa significant contribution between upper limb muscle strength, trunk flexibility, and leg power against movement totiger jump with Fhitung 11,001 Ftabel 2,794.Keywords: Contribution, Strength, Flexibility